Job Stress Level Among Public Bank Employees at Selected Branches in Kuching, Sarawak. - Petrus Clay, Jimel (2006)
Stress is an emergent occupational problem in the modern society. Contending with stressful situations in the workplace is a common occurrence for all employees particularly in a service industry The purpose of this study was to survey the level of job stress among the Public Bank's employees at three selected branches in Kuching, Sarawak. In addition, the study also attempted to determine if there were any statistically significant differences in the respondents' level of job stress when grouped by gender, educational level, ,job category and branches. Job Stress Survey (Spielberger & Vagg, 1999) was adopted for this study. A total of 63 employees participated in this survey. The findings of this study showed that the overall job stress level of the selected samples was 'high '. There was no statistically significant difference in the level of job stress by gender and job category. However, the findings showed that there was a statistically significant difference in the job stress level of respondents when grouped by educational qualification Bank employees with SPM qualification experienced higher job stress level than those with STPM background.The SPM holders perceived Lack of Organizational Support stressors as more severe than the job pressure stressors.